Aplikasi Playstore Sex Education Islamic untuk Pencegahan Pelecehan Seksual Anak - Maharani, Rosytania Fitri; Wulandari, Murfiah Dewi (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2023)
Background: Victims of sexual victims are dominated by children and has increased every year. Islam teaches sex education to children which is contained in the Qur'an and Al Hadith. This is used as a guide for sexual prevention in children. This study aims to determine the effectiveness of Islamic Sex Education (SEI) media in increasing children's self-protection from sexual intercourse. Method: This research is a quasi-experimental research with a pretest-posttest control group design. The population used in this study was grade VI SD Muhtadin Madiun City with a total of 55 students in the academic year 2021/2022. The sample in this study was class VI A students who collected 19 students as the experimental class. While class VI B which opened 18 students as a control class. The data collection technique uses the WIST instrument that has been adapted and documentation. Result: The results of the research that have been tested for the hypothesis that the value of Sig. (2-Tailed) 0.027 < 0.05 there is an influence of Islamic Sex Education (SEI) media in increasing children's self-protection against class VIA at Muhtadin Elementary School, Madiun City. Conclusion: It can be said that the results of this study of Islamic Sex Education (SEI) media are effective in increasing sexual self-protection. The effectiveness of SEI media, which is 77%, is included in the high category.